Fun, community, and culture in a Japanese alternative food network - Black, Jasmine E. (Frontiers in Sustainable Food Systems, 2024)
Introduction Alternative Food Networks (AFNs) are important sources of community-driven sustainable food production and consumption. It is apparent that despite the existing environmentally friendly ways of producing food, such networks are not yet multiplying at a rate which could help tackle climate change and biodiversity loss. This study is set in Sado island, Japan, which has become well known for its farming practices protecting the crested ibis, as well as its GIAHS status, but which also has an AFN beyond these accreditations. It investigates the challenges and opportunities of Sado’s AFN to find ways to help it thrive, and give potential pointers for developing new AFN’s. Methods In this research I use a mix of experiential sensory ethnography, socially-engaged art and interviews to understand the challenges and opportunities of an AFN in Sado island, Japan. A range of Sado’s AFN actors were engaged to provide a more holistic picture. Results Young and new entrant farmers, food processors and retailers in Sado expressed the need for their work to be fun as well as in coexistence with nature, using innovative practices and models to make this a reality. AFN actors also revealed a great capacity to undertake numerous food and culture related events, for the purpose of community, throughout the year. Despite this, there are gaps in capacity, and a lingering negative image of farming and rural areas as difficult places to live. These factors are stemming the ability for new AFNs to begin and existing ones to thrive. Discussion Giving farming a fun, empowering and positive image whilst creating greater networking capacity could strengthen this AFN and help create new ones in other ruralities. Further, better acknowledging the importance of the culture and arts through which people connect to nature could form a greater source of pride and motivation to stay in rural areas.